Pursuing a New Order I. - Rychterová, Pavlína (Brepols, 2018)
Concentrating on the period of the emergence of the vernaculars in the context of religious text production in Central and Eastern Central Europe from the fourteenth to the sixteenth centuries, the individual studies in this volume present material so far neglected by nationally defined historiographies and literary studies. The process of vernacularization created a new sociolinguistic field for the negotiation of social order through the choice of texts and topics. This volume seeks to answer the questions of whether, why and how distinctive new communicative, literary, and political cultures developed after the vernacular languages had acquired ever higher levels of literacy and education. The volume fills a gap in contemporary scholarship on the role of the vernaculars and vernacular literatures in European medieval societies and with the focus on Eastern European regions it breaks new ground in regard to questions that have so far only been explored on the basis of material from Europe’s ‘West’.